2017
DOI: 10.1371/journal.pone.0182415
|View full text |Cite
|
Sign up to set email alerts
|

Reduced internalization of TNF-ɑ/TNFR1 down-regulates caspase dependent phagocytosis induced cell death (PICD) in neonatal monocytes

Abstract: Phagocytosis-induced cell death (PICD) is diminished in cord blood monocytes (CBMO) as compared to cells from adults (PBMO) due to differences in the CD95-pathway. This may support a prolonged pro-inflammatory response with sequels of sustained inflammation as seen in neonatal sepsis. Here we hypothesized that TNF-α mediated induction of apoptosis is impaired in CBMO due to differences in the TNFR1-dependent internalization. Monocytes were infected with Escherichia coli-GFP (E. coli-GFP). Monocyte phenotype, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
(46 reference statements)
1
16
0
Order By: Relevance
“…We show that cell surface EGFR is increased in response to E. coli infection ( Figure 2(a) ), matching the results of another study that demonstrated upregulation of EGFR upon Helicobacter pylori infection [ 46 ]. It was already shown that TNF- α induces upregulation of EGFR [ 47 ], and in a previous study, we demonstrated that E. coli infection leads to TNF- α release, while PBMO displayed a distinctly increased TNF- α release compared to CBMO [ 48 ]. Therefore, we hypothesize that the increase in EGFR might be caused by E. coli infection and subsequent TNF- α release, thereby amplifying AREG function.…”
Section: Discussionmentioning
confidence: 82%
“…We show that cell surface EGFR is increased in response to E. coli infection ( Figure 2(a) ), matching the results of another study that demonstrated upregulation of EGFR upon Helicobacter pylori infection [ 46 ]. It was already shown that TNF- α induces upregulation of EGFR [ 47 ], and in a previous study, we demonstrated that E. coli infection leads to TNF- α release, while PBMO displayed a distinctly increased TNF- α release compared to CBMO [ 48 ]. Therefore, we hypothesize that the increase in EGFR might be caused by E. coli infection and subsequent TNF- α release, thereby amplifying AREG function.…”
Section: Discussionmentioning
confidence: 82%
“…In the context of apoptosis, TNF-TNFR1 axis signals through caspase 3 and 8, and is mainly responsible for the host defense of pathogen ( 43 ) and anti-tumoral activities ( 44 ). The impaired regulation of this TNF receptor can cause autoimmune diseases, cancer, chronic infections and allergy ( 45 ).…”
Section: Pathogenic Role Of Tnf In Allergic Manifestationmentioning
confidence: 99%
“…One recent study showed that TNF-α can mediate cell death by ligating its receptor TNF receptor 1 (TNFR1) and uptake of ligand-bound TNFR1 activates caspase-8 and -3 in cord blood monocytes. 29 The reduced levels of bax in this study suggest a different apoptosis pathway induced by TNF-α after SAH. Collectively, these results strongly suggest the differential molecular mechanisms of action for anti-TNF-α antibody in different brain regions during the inhibition of apoptosis after SAH.…”
Section: Discussionmentioning
confidence: 60%